Ingroup Love or Outgroup Hate (or Both)? Mapping Distinct Bias Profiles in the Population. (February 2020) - Hamley, Logan; Houkamau, Carla A.; Osborne, Danny; Barlow, Fiona Kate; Sibley, Chris G.
Researchers have long argued that ingroup favoritism and outgroup derogation are separable phenomena that occur in different, meaningful combinations. Statistical methods for testing this thesis, however, have been underutilized. We address this oversight by using latent profile analysis (LPA) to investigate distinct profiles of group bias derived from ingroup and outgroup warmth ratings. Using a national probability sample of Māori (the indigenous people of New Zealand; N = 2, 289) and Europeans ( N = 13, 647), we identify a distinct profile reflecting ingroup favoritism/outgroup derogation (Type III in Brewer's typology of ingroup bias) in both groups (6.7% of Māori, 10.3% of Europeans). The factors associated with this type, however, differed between groups. Whereas ethnic identity centrality predicted membership for Type III for Māori, social dominance orientation predicted this type for Europeans. Thus, although both groups may express the same kind of bias pattern, the motivation underlying this bias varies by status.